Hubungan Antara Nyeri, Kecemasan Dan Lingkungan Dengan Kualitas Tidur Pada Pasien Post Operasi Apendisitis - Ummami Vanesa Indri; Darwin - Karim; Veny - Elita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The purpose of this study was to determine the relationship between anxiety, pain, and environment with sleep quality in patients with postoperative appendicitis. This study used a descriptive design with cross-sectional correlation. The sample of this research was the patient with postoperative appendicitis at Arifin Achmad Hospital, the number of samples is 54 respondents were taken using a consecutive sampling technique. Instruments used in this research was a questionnaire that had been tested for validity and reliability. Data analysis used univariate and bivariate analysis using Chi Square test. The results showed that there is an correlation between pain and anxiety with sleep quality appendicitis postoperative patients (p value = 0.000, 0.000) and there is no relationship between the environment and the quality of sleep in patients with postoperative appendicitis (p value = 0.828). Based on the result of this research advised to the health care provider especially nurses to increase health care and patient needs. Keywords : Anxiety, environmental, quality, pain